(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
This article summarizes current data on the impact of various dietary patterns on inflammatory markers and their relationship with insulin resistance. The effects of the Mediterranean, low-carbohydrate, high-fiber, and anti-inflammatory diets are examined. Diets high in fiber, antioxidants, and monounsaturated fats have been shown to reduce levels of TNF-α, IL-6, and CRP, contributing to improved insulin sensitivity. Limiting saturated fats and sugars further reduces inflammation and lowers the risk of insulin resistance progression.